THE EFFECT OF PAY SATISFACTION ON TURNOVER INTENTION MEDIATED BY ORGANIZATIONAL COMMITMENT - Noly Hendry; Zakhyadi Ariffin (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the effect of salary satisfaction on turnover intention mediated by organizational commitment on employees at PT Nusantara Food Asia. The main problem faced is the high turnover intention of employees due to dissatisfaction with salary, which has an impact on productivity and the sustainability of company operations. This study uses a quantitative approach with a survey method through a questionnaire, where the population consists of 67 permanent employees. The variables analyzed include salary satisfaction as an independent variable, organizational commitment as a mediating variable, and turnover intention as a dependent variable. Data analysis was carried out using the Partial Least Square (PLS) method. The results showed that salary satisfaction has a significant effect on decreasing turnover intention, both directly and through increasing organizational commitment. Employees who are satisfied with compensation show higher commitment and tend to have lower turnover intentions. This study provides recommendations for companies to increase salary satisfaction and organizational commitment to reduce turnover intention. Fair and competitive compensation strategies and strengthening organizational culture are expected to increase employee retention and company stability.